The Traditional and Pharmacological Properties of Solanum nigrum: a Review - Mani, Rupesh Kumar; J B, Paramashree; D R, Bharathi; Ahmed, Syed Sagheer (International Journal of Indigenous Herbs and Drugs, 2022)
Solanum nigrum has a place in the Solanaceae family with a common name of garden nightshade. It is composed of a variety of glycoalkaloids, glycoproteins, polysaccharides and polyphenolic mixtures such as gallic acid, catechin, protocatechuic acid, and caffeic acid, epicatechin, and rutin. Solanum nigrum have hepatoprotective, antitumor, immunomodulatory, anti-ulcer, calming, hostile to convulsant, cardio defensive, antibacterial, antidiabetic and pain-relieving impacts. Traditional medicine in India and other parts of the globe has used Solanum nigrum to treat liver disorders, constant skin sickness, fiery circumstances, menstrual cramps, fevers, diarrhoea, eye infections, dizziness and other diseases.